18F-Sodium Fluoride Imaging of Coronary Atherosclerosis in Ambulatory Patients With Diabetes Mellitus. Issue 2 (February 2019) - Raggi, Paolo; Senior, Peter; Shahbaz, Shima; Kaul, Padma; Hung, Ryan; Coulden, Richard; Yeung, Roseane; Abele, Jonathan
Abstract : Objective—: Although patients with diabetes mellitus (DM) are considered at high risk of cardiovascular events, there is growing evidence that this notion is incorrect. Atherosclerosis imaging may identify patients at risk. Approach and Results—: We performed coronary atherosclerosis with 18 F-sodium fluoride (NaF) positron emission tomography/computed tomography and gated chest computed tomography for coronary artery calcium in 88 consecutive ambulatory patients with DM on a stable medical regimen. NaF has been shown to localize avidly in culprit lesions of patients with acute coronary syndromes and may identify unstable plaques. NaF activity was measured as target (coronary arteries)-to-background (left ventricular pool) ratio (TBR). High TBR was defined as ≥1.5. The mean age of the cohort was 54±14 years, 55% had type 2 DM, 65% were men, the median HgbA1c (hemoglobin A1c) and LDL (low-density lipoprotein) cholesterol were 7.5% (interquartile range, 7.1–8.5) and 1.9 mmol/L (interquartile range, 1.5–2.6), respectively. Mean coronary artery calcium score was 374±773, and median TBR was 1.2. Coronary artery TBR ≥1.5 was detected in 13 (15%) patients. In univariable analyses, male sex ( P =0.0002), estimated glomerular filtration rate ( P =0.02), and total coronary artery calcium score ( P =0.04) were associated with TBR. In multivariable analyses, TBR >median was associated with male sex ( P =0.0001) and statin use ( P =0.042). Conclusions—: In ambulatory patients with DM asymptomatic for cardiovascular disease, the prevalence of potentially vulnerable plaques detected with NaF was low, but in the absence of follow-up data at this stage, we cannot assess the import of this information. Future research will establish whether NaF imaging helps risk stratify patients with DM. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT03530176.